Beresford, Andrew M. Sacred Skin: The Legend of St. Bartholomew in Spanish Art and Literature. Brill, 2020. [ISBN: 978-90-04-40780-0] - Grau-Dieckmann, Patricia (Eikón / Imago, 2024)
Book review: Beresford, Andrew M. Sacred Skin: The Legend of St. Bartholomew in Spanish Art and Literature. Brill, 2020. [ISBN: 978-90-04-40780-0]